Unilateral and Bilateral Post-Activation Performance Enhancement on Jump Performance and Agility (2021)
ABSTRACT: This study aimed to compare the effects of the post-activation performance enhancement (PAPE) of two different types of warm-ups, unilateral and bilateral, on the performance in vertical jumping and agility of healthy subjects with strength training experience. In the study, 17 subjects (12 men and 5 women) performed two different PAPE protocols: unilateral squat (UT) and bilateral squat (BT). The height of the subjects’ countermovement jump (CMJ) and the subjects’ time to perform the T-agility test (TAT) were measured before and after executing the PAPE warm-up. The squats were performed at a velocity of 0.59 m·s−1 with three sets of three repetitions, with a 3-min rest between sets and a 5-min rest after both uni- and bilateral PAPE warm-ups before taking the tests again. For statistical analysis, we applied ANOVA and calculated the effect size. The results showed that the PAPE for each case decreased the CMJ height but generated significant improvements in the total time taken for the T-agility test (p < 0.01); however, in both cases, the effect sizes were trivial. In conclusion, it is possible to observe that the PAPE, performed both unilaterally and bilaterally, negatively affects the performance in the vertical jump, showing moderate effect sizes. However, both PAPE protocols show performance benefits in agility tests, with a large effect size for the unilateral protocol and moderate for the bilateral protocol.